Ashwagandha (Withania somnifera) - influence on sleep: review - Jędruszczak, Przemysław; Zdun, Sylwia; Walczak, Klaudia; Wesołowska, Zuzanna; Gaweł, Weronika (Quality in Sport, 2023)
Introduction: Ashwagandha (Withania somnifera) is a plant found on the Indian subcontinent. The health-promoting properties attributed to it have been largely verified in numerous studies over the past 20 years. This article reviews studies on the effects of ashwagandha supplementation on sleep, its deprivation, and studies analyzing the mechanisms determining such effects. Materials and methods: A review of the literature available in the PubMed database was carried out, using the key words: "ashwagandha" ; "sleep" ; "insomnia", "withania", "somnifera", "withanolide", "withaferin". Results: Ashwagandha has a positive effect on the quality and length of sleep. It is indicated that it improves sleep parameters among both insomniacs and healthy people. In addition, it has been proven to reduce oxidative stress under conditions of sleep deprivation. Ashwagandha's positive effects on sleep have been shown to be related to its effects on GABA-nergic transmission, and the chemical responsible for the plant's sleep induction is triethylene glycol. Its regular use increases dopamine levels in the brain and could potentially be useful in treating the sleep-related disorder restless legs syndrome. Conclusions: The use of ashwagandha is a potential direction for treating sleep disorders and improving sleep quality in healthy individuals. There is a need for further development and studies on larger groups of patients to exploit its potential.